Censorship Dalam Ekosistem Perbukuan Di Kota Padang - M. Irfan Fadli; Yona Primadesi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe sensors in the book ecosystem in Padang City. This research is qualitative research with descriptive methods. The technique for determining informants is purposive sampling, namely a method of identifying informants with certain considerations. Data collection techniques were carried out using observation, interviews and documentation methods. This research uses data dependability. The results of this research show that (1) forms of censorship practices in Padang City. In this research it was found that there were 3 forms of censorship practices carried out, namely; Costitutive censorship, regulative censorship, independent censorship. (2) the influence of censorship in the book ecosystem in the city of Padang. In this research, it was found that writers, illustrators, publishers and bookstores believe that the practice of censorship (censorship) can reduce the intelligence of the people of a nation because they are always surrounded by fear in producing books.